1991
DOI: 10.1086/296523
|View full text |Cite
|
Sign up to set email alerts
|

The Survival of Noise Traders in Financial Markets

Abstract: We present a model of portfolio allocation by noise traders with incorrect expectations about return variances. For such misperceptions, noise traders who do not affect prices can earn higher expected returns than rational investors with similar risk aversion. Moreover, such noise traders can come to dominate the market, in that the probability that they eventually have a high share of total wealth is close to one. Noise traders come to dominate despite their taking of excessive risk and their higher consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
171
1
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 483 publications
(187 citation statements)
references
References 26 publications
(23 reference statements)
11
171
1
4
Order By: Relevance
“…Therefore, we model the development of the average noise traders' mood ξ as a random walk with increments η. This choice of the type of stochasticity governing the noise traders' behavior is different from the related literature, in particular the paper of De Long et al [10], where the misperseption of the noise traders itself is modeled as an iid random variable. The random walk assumption, however, avoids the abrupt variations of the market price, which would occur if we would incorporate the De Long formalization.…”
Section: Market Implementationmentioning
confidence: 91%
See 3 more Smart Citations
“…Therefore, we model the development of the average noise traders' mood ξ as a random walk with increments η. This choice of the type of stochasticity governing the noise traders' behavior is different from the related literature, in particular the paper of De Long et al [10], where the misperseption of the noise traders itself is modeled as an iid random variable. The random walk assumption, however, avoids the abrupt variations of the market price, which would occur if we would incorporate the De Long formalization.…”
Section: Market Implementationmentioning
confidence: 91%
“…N C noise traders, who are subject to "irrational" fads and moods, following the seminal contribution by De Long et al [10].…”
Section: Market Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent literature, there is still an ongoing debate. By using a partial equilibrium setting, De Long et al (1991) showed that agents with inferior beliefs may survive in the long run. This is because agents with modestly optimistic beliefs will bear more risk than those agents who hold the correct beliefs and, as a result, earn greater risk premium and grow their wealth on average at a higher rate.…”
Section: Natural Selectionmentioning
confidence: 99%